2002
DOI: 10.1037/0022-3514.83.6.1314
|View full text |Cite
|
Sign up to set email alerts
|

The police officer's dilemma: Using ethnicity to disambiguate potentially threatening individuals.

Abstract: Using a simple videogame, the effect of ethnicity on shoot/don't shoot decisions was examined. African American or White targets, holding guns or other objects, appeared in complex backgrounds. Participants were told to "shoot" armed targets and to "not shoot" unarmed targets. In Study 1, White participants made the correct decision to shoot an armed target more quickly if the target was African American than if he was White, but decided to "not shoot" an unarmed target more quickly if he was White. Study 2 us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
879
6
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 925 publications
(963 citation statements)
references
References 51 publications
55
879
6
2
Order By: Relevance
“…Such implicit bias leads to actual perceptions of racial stigma and ecological contamination whereby individuals view all persons (e.g., Blacks) living in a geographical area as threatening, dangerous, and violent (e.g., culture of violence). In a recent experimental study with police officers, Correl, Park, Judd, and Wittenbrink (2002) tested the power of implicit bias by conducting shoot/don't shoot exercises with police officers who were instructed to shoot armed and not to shoot unarmed targets. The findings indicated that officers responded more quickly to shooting an armed target when such target represented an African American as opposed to a White target.…”
Section: Discussionmentioning
confidence: 99%
“…Such implicit bias leads to actual perceptions of racial stigma and ecological contamination whereby individuals view all persons (e.g., Blacks) living in a geographical area as threatening, dangerous, and violent (e.g., culture of violence). In a recent experimental study with police officers, Correl, Park, Judd, and Wittenbrink (2002) tested the power of implicit bias by conducting shoot/don't shoot exercises with police officers who were instructed to shoot armed and not to shoot unarmed targets. The findings indicated that officers responded more quickly to shooting an armed target when such target represented an African American as opposed to a White target.…”
Section: Discussionmentioning
confidence: 99%
“…In another perceptual effect of race, participants are more likely to misperceive a tool as a weapon after being primed with an African American face (see also Eberhardt, Goff, Purdie, & Davies, 2004;Payne, 2001). In a similar vein, participants taking part in a computer game where they have to shoot only those people who carry a gun are more likely to accidentally shoot black computer avatars carrying tools than white avatars (Correll, Park, Judd, & Wittenbrink, 2002), an effect that also holds for avatars with Muslim headgear (Unkelbach, Forgas, & Denson, 2008). So far we have given an overview of studies that explored the interaction between high level social knowledge and low-level perceptual processes (for an overview of the effects of non-social high-level factors and perception, please see Vetter & Newen, 2014).…”
Section: Social Perceptionmentioning
confidence: 99%
“…Likewise, studies show that characteristics of other virtual characters, such as gender (Guadagno, Blascovich, Bailenson, & McCall, 2007), or aspects of the interpersonal RUNNING HEAD: Virtual Violence and Guilt 6 virtual setting, such as interpersonal distance (Bailenson, Blascovich, Beall, & Loomis, 2003), influence the way users perceive and interact with these characters socially. In a study by Correll, Park, Judd, and Wittenbrink (2002), participants were required to shoot armed soldiers in a simple video game. Results showed that White participants shot armed African American soldiers more quickly than White soldiers, suggesting that the ethnicity of the virtual characters activated participants' stereotypes.…”
Section: Different From Playing Chess: the Moral Significance Of Virtmentioning
confidence: 99%